Karakteristik Habitat Kura-kura Hutan Sulawesi Berstatus Kritis Leucocephalon yuwonoi Di Kawasan Sungai Ganonggol Dan Bangkir, Sulawesi Tengah - Riyanto, Awal; Soemarno, Suprayogo; Wawangningrum, Hary; Partomihardjo, Tukirin (Perhimpunan Biologi Indonesia, 2006)
ABSTRACTThe Habitat Characteristic of the Critically Endangered Turtle the Sulawesi ForestSulawesi Turtle Leucocephalon yuwonoi in Ganonggol and Bangkir Rivers in CentralSulawesi. The Sulawesi Forest Turtle (Leucocephalon ymonoi) is an endemic, criticallyendangered and listed in the appendix I1 of CITES. Captive breeding is needed toreintroduce the species into the original habitat. Captive breeding success includes acomprehensive knowledge on the biology and ecology of the species. The objective ofthis research is to investigate the habitat character of the turtle respectively vegetation ofthe riverbank, physical and chemical conditions ofthe water. Field surveys were conductedon the Moutong area from 1 l until 19 October 2004 and on the Bangkir area from 20until 26 October 2004. Vegetation data were obtained by developing four quadrate at theturtle habitat in each locality and were analyzed using Curtis method. The results shownthat the habitat of Leucocephalon yuwonoi is transparent streaming water, neutral, nottoo high dissolved oxygen, water height not more than 50 cm, substrat varies from bigstones, small stones, clay loam and sandy loam. The area was covered by vegetation thatcan provide food during all year round, such as Colocasia esculenta, Limnocharisflava,and Ipomoea aquatics.Key Word: Leucocephalon yuwonoi, habitat, vegetation, water conditions.